Pelatihan Public Speaking Bagi Jemaat HKBP Karawang - Verdinand Robertua; Indah Novitasari; Angel Damayanti; Singgih Sasongko (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2021)
Public speaking skills for church community is very important in facing the new challenges in the digital age. Faculty of Social and Political Science Universitas Kristen Indonesia organized community service activity in the form of public speaking workshop to HKBP Karawang community member on Friday, 23 April 2021. The public speaking was conducted by the presentation and the simulation. After the training was completed, the participant filled the project satisfaction survey. The survey was analyzed using SPSS. The result showed that the participants were satisfied with the training and were recommended to be followed by subsequent training. Keywords: public speaking training, HKBP Karawang, Fisipol UKI